The effort–reward imbalance model in policing: associations with mental health and work functioning among sworn and civilian employees - Bjørn Lau; Knut Inge Fostervold; Brita Bjørkelo (International Archives of Occupational and Environmental Health, 2026)
Abstract Objective The Effort–Reward Imbalance (ERI) model is widely used to explain work-related stress and its health consequences. In policing, ERI research has primarily focused on sworn officers, while civilian employees have received limited attention. The purpose of this study was to examine whether ERI variables are associated with mental health and occupational functioning among police employees, and whether these associations differ between sworn officers and civilian personnel. Methods This cross-sectional study included sworn police officers and civilian employees in the Norwegian police. A random sample of 4000 employees was invited to complete an online survey, and 560 employees participated. Effort, reward, and overcommitment were measured with the 16-item short ERI questionnaire, and the ERI ratio was calculated from the effort and reward scales. Anxiety symptoms, depressive symptoms, work engagement, and job-related self-efficacy were assessed using separate questionnaires. Group differences were examined using analyses of covariance, and associations between ERI predictors and outcome variables were tested using hierarchical regression analyses with interaction terms for occupational role. Results In the covariate-adjusted analytic sample (N = 558), no significant differences were observed between sworn officers and civilian employees in ERI variables, mental health outcomes, or occupational functioning. Higher ERI ratio was associated with higher anxiety symptoms (β = 0.28) and depressive symptoms (β = 0.33) and with lower work engagement (β = − 0.27) and job-related self-efficacy (β = − 0.16). Overcommitment showed stronger associations with anxiety symptoms (β = 0.50) and depressive symptoms (β = 0.46) and was inversely associated with job-related self-efficacy (β = − 0.28) and work engagement (β = − 0.14). Occupational role did not moderate these associations. Conclusions The findings support the ERI model by demonstrating consistent associations between effort–reward imbalance, overcommitment, mental health, and occupational functioning in policing. Neither the levels of the ERI variables nor their associations with the outcomes differed by occupational role, suggesting that ERI processes operate similarly across occupational categories within a highly regulated welfare-state context.